A prospective study on correlation of high-resolution computed tomography temporal bone and surgical findings in squamosal chronic otitis media - Parveen, Mehvish; Ahmed, Aftab; Sharma, Satish C.; Khalid, Saifullah; Monis, M. (International Journal of Research in Medical Sciences, 2025)
Background: Chronic otitis media (COM) is a common condition seen in patients attending ENT department. It is caused by persistent inflammation of the middle ear and mastoid cavity and when left untreated, can lead to significant complications, including the development of squamosal chronic otitis media (SCOM). The aim of this study is to assess the role of high-resolution computed tomography (HRCT) temporal bone in preoperative evaluation of squamosal chronic otitis media. Methods: This study is a prospective study involving 50 cases of COM. All the patients underwent pre-operative HRCT followed by surgical exploration of middle ear cleft to compare the HRCT findings with the operative findings, thereby establishing a robust correlation between radiological assessment and surgical observations. Results: The result of the study reveals varying levels of agreement between CT and operative findings across different structures, with generally high concordance rates and statistically significant p values, indicating the reliability of CT in diagnosing these conditions. All findings are statistically significant, emphasizing the consistency between CT and operative findings. The result also highlights that CT scans have high levels of reliability in detecting ossicular erosion, various types of malleus erosion, with good to very good agreement for head of malleus and handle of malleus erosion. Conclusions: The study highlights the potential of HRCT to improve surgical outcomes by enabling more precise and targeted interventions, ultimately leading to better eradication of the disease from the middle ear cleft.